A Comparison of the Chemical Composition of Flowering Shoot Thymus kotschyanus and Thymus vulgaris by using GC-Mass and Antimicrobial Effects of the Bacteria Staphylococcus aureus and Pseudomonas aeruginosa. Issue 7 (2nd October 2016) - Zhiani, Rahele; Dolatabadi, Samaneh; Imani, Hadise; Moradi, Marjan; Emrani, Shokufe
Abstract: Thymus, an aromatic plant of the family lamiaceae, has valuable medicinal properties commonly used in traditional and modern medicine across the world. This plant is mainly native to the northern temperate regions such as southern Europe and Asia. In Iran, several species of this plant grows in most of the temperate and mountainous areas. In this study, chemical compounds of flowering shoot of two types of thyme, namely Thymus vulgaris and Thymus kotschyanus, are compared. Thymus vulgaris was collected from the herbal plants farm of Science and Culture University of Kashmar, and Thymus kotschyanus was collected from the heights of Bojnurd. Water and steam distillation methods were performed in order to collect the essential oils. Compounds of essential oils were identified using gas chromatography coupled with mass spectrometry GC-MASS. There were 10 common compounds identified: γ-terpinene, thymol, α-pinene, camphene, oleic acid, 1-octen-3ol, trans -caryophyllene, β-myrcene, α-thujene, 1, 8-cineole. Thymol was present in the essential oil and had the highest percentage, which was found to be at its highest in the flower bud of T. vulgaris at 54.66%. The antimicrobial properties of these plants were measured by the Disk diffusion method against two bacteria. It was discovered that T. vulgaris were found to have strong antimicrobial properties. The essential oils were more sensitive against Staphylococcus aureus than Pseudomonas aeruginosa .